A Discussion of Stability and Engineering Verification of Thin Immediate Roof under Uniform Load of the Rectangular Coal Roadway - Linsheng Gao; Yueping Wang; Er-hui Zhang; Liang Cheng; Rui Peng (Advances in Civil Engineering)
Roadway roof is a key factor in roadway stability. At present, the analysis of roof stability is mainly based on numerical calculations and field measurements with a relatively weak theoretical basis and inadequate research studies on the loading mechanism of the roof. In this paper, a mechanical calculation model of immediate direct roof under uniform load of rectangular coal roadway is established. The stress distribution and roof subsidence in the roof are calculated theoretically and verified by the numerical calculation, physical tests, and engineering applications. Based on the classical beam solution theory, the stress distribution and sinking of the thin immediate roof under uniform load are obtained and verified by numerical calculations. The results are highly consistent. Two types of thin direct roof failure under uniform load are analyzed: the failure of the normal cross section caused by the bottom tensile stress and the failure of the inclined section caused by the combined effect of the tensile stress in the abdominal area and compressive stress. The stability of thin immediate roof under uniform load of the rectangular coal roadway was tested in 1905s mining roadway of Great Wall Number #3 coal excavation field. This research can further fill in blanks of the loading mechanism of the roadway roof and provide theoretical and pragmatic values to control the roadway pressure and rock stratum as well as the scientific references to the design of the anchor bolt supporting system.